2019
DOI: 10.1038/s42255-019-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

NADPH production by the oxidative pentose-phosphate pathway supports folate metabolism

Abstract: NADPH donates high energy electrons for antioxidant defense and reductive biosynthesis. Cytosolic NADP is recycled to NADPH by the oxidative pentose phosphate pathway (oxPPP), malic enzyme 1 (ME1) and isocitrate dehydrogenase 1 (IDH1). Here we show that any one of these routes can support cell growth, but the oxPPP is uniquely required to maintain a normal NADPH/NADP ratio, mammalian dihydrofolate reductase (DHFR) activity and folate metabolism. These findings are based on CRISPR deletions of glucose-6-phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
313
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(327 citation statements)
references
References 43 publications
12
313
1
1
Order By: Relevance
“…Cancer cells express pyruvate kinase 2 (PKM2), a growth signal-sensitive form of the rate-limiting enzyme in the last step of glycolysis 3 , leading to the accumulation of glycolytic intermediates. The accumulated glycolytic intermediates can branch into the PPP for nucleotide biosynthesis and NADPH production, which is important for cell proliferation and redox state maintenance 4 . The PPP is highly upregulated in cancers to meet the needs of uncontrolled cell proliferation 5,6 .…”
mentioning
confidence: 99%
“…Cancer cells express pyruvate kinase 2 (PKM2), a growth signal-sensitive form of the rate-limiting enzyme in the last step of glycolysis 3 , leading to the accumulation of glycolytic intermediates. The accumulated glycolytic intermediates can branch into the PPP for nucleotide biosynthesis and NADPH production, which is important for cell proliferation and redox state maintenance 4 . The PPP is highly upregulated in cancers to meet the needs of uncontrolled cell proliferation 5,6 .…”
mentioning
confidence: 99%
“…The pentose phosphate pathway (PPP) is a major contributor to the cellular NADPH pool [ 41 ]. NADPH is critical for the synthesis of fatty acids, cholesterol, mevalonate pathway products [ 42 ], nucleotides, folate [ 41 , 43 ], and proline [ 40 ], all of which can support tumorigenesis. NADPH is also important for survival during ROS-mediated stress as a result of extracellular matrix (ECM) detachment [ 44 ].…”
Section: Modulation Of Metabolic Processes By Nrf2mentioning
confidence: 99%
“…Overall, these studies demonstrate the importance of KEAP1 mutational status when evaluating sensitivity to PPP inhibition in a therapeutic context. However, recent work suggests that the oxidative PPP plays a unique role in folate metabolism [ 41 ]. Chen et al demonstrated that while the PPP, IDH1 and ME1 could all support cellular proliferation, only the PPP could maintain a normal NADPH/NADP+ ratio.…”
Section: Modulation Of Metabolic Processes By Nrf2mentioning
confidence: 99%
“…Catalases and the glutathione pathway which scavenge ROS from the cell require NADPH ( Toledano et al, 2013 ; Gómez et al, 2019 ). Interestingly, not only are oxidative stress response proteins differentially expressed during treatment with phenolic inhibitors, as revealed in a proteomics screen, but also flux is moved toward the pentose phosphate pathway ( Lv et al, 2014 ), one of the main metabolic pathways that generate cytosolic NADPH ( Chen et al, 2019 ). Indeed, this proteomic study is corroborated by a functional genomic screen which showed that pentose phosphate pathway mutants accumulated ROS and were hypersensitive to coniferyl aldehyde ( Fletcher et al, 2019 ).…”
Section: Mining Genome-wide Studies To Identify Common Approaches To mentioning
confidence: 99%